Effect of Farm Management Practices on Morbidity and Antibiotic Usage on Calf Rearing Farms - Atte Sandelin; Outi Hälli; Heidi Härtel; Tuomas Herva; Liisa Kaartinen; Erja Tuunainen; Helena Rautala; Timo Soveri; Heli Simojoki (MDPI AG, 2022)
Antimicrobial resistance has been recognized as one of the top health threats to human society. Abundant use of antibiotics in both humans and animals has led to ever-increasing antibiotic resistance in bacteria. In food production, decreasing morbidity in beef herds would be an effective way to reduce the use of antibiotics. The objective of this retrospective observational study was to determine overall morbidity on calf rearing farms and to identify associated risk factors. Data were collected by questionnaire, meat companies' databases and the national cattle register for 28,228 calves transported to 87 calf rearing farms. All medications given to these calves were retrospectively followed for 180 days from calf arrival to the farm. In total, 34,532 parenteral antibiotic medications were administered to the 28,228 study calves (122.3%), and 17,180 calves (60.9%) were medicated with antibiotics at least once during the follow-up. Higher numbers of calves transported to the same farm and larger age variation in calves in the same arrival batch were both associated with increased morbidity. In contrast, higher arrival age of individual calves was associated with decreased morbidity. Our study identifies several factors to consider in decreasing morbidity and antibiotic usage on calf rearing farms.